THE EFFECT OF ISLAMIC VALUES-BASED STORYTELLING ON LITERACY DEVELOPMENT IN MADRASAH IBTIDAIYAH STUDENTS - Novria Grahmayanuri; Shoufi Nisma Dewi; Siti Khodijah; Devi widya Ningsih; Nurhayati (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study investigates the effect of Islamic values-based storytelling on literacy development among fourth-grade of Madrasah Ibtidaiyah Negeri Medan Sunggal in Medan. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants were 30 students selected through purposive sampling. Data were collected through literacy tests administered before and after the treatment. The storytelling intervention was conducted over several meetings using Islamic narratives containing values such as honesty, patience, responsibility, and kindness. Data were analyzed using descriptive statistics and a paired sample t-test. The findings showed that students’ literacy development improved significantly after the intervention. The mean score increased from 62.40 in the pre-test to 81.20 in the post-test. The paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating that Islamic values-based storytelling had a significant effect on students’ literacy development. In addition, students demonstrated increased engagement as indicated by and active participation during the learning process. In conclusion, Islamic values-based storytelling is an effective strategy for improving students’ literacy skills while promoting moral understanding and character development in Madrasah Ibtidaiyah classrooms.